THE AIRPORT MANAGEMENT IN MODERN CONDITIONS - Chyhasova, N. M. (Science and Transport Progress, 2007)
The value of air-port is considered as parts of the aviation transporting system. The analysis of structures of management by air-ports is executed. Macroeconomic indexes influencing on air transportations are adopted.